A New Approach of Several Minimally Invasive Procedures for Improvement of the Outcome in Preterm Infants - Radulova, Petya; Hitrova-Nikolova, Stanislava; Vakrilova, Liliya; Dimitrova, Violeta (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Based on the last update of European Consensus Guidelines on Management of Respiratory Distress Syndrome, the following study is new for our clinic approach for minimally invasive respiratory support in preterm infants. AIM: The aim is to find out if the implementation of several minimally invasive procedures leads to a reduction of the frequency and severity of chronic complications and improved outcomes in extremely premature infants. MATERIALS AND METHODS: Infants are below 30 gestational weeks, divided into two groups – therapeutic – 37 infants on standardized early respiratory management protocol which includes: High-flow continuous positive airway pressure (20l/min ≥ 15 PEEP) in the delivery room, support of spontaneous breathing and non-invasive mechanical ventilation, avoidance of hypothermia and LISA shortly after birth, and control group – 46 infants that received standard respiratory support (positive pressure ventilation – invasive and non-invasive in the delivery room, most infants ≤ 27 weeks gestational age were intubated and received early surfactant, extubation “when being ready” – usually after few days). RESULTS: The duration of mechanical ventilation, oxygen therapy, and hospital stay is shorter in the therapeutic group (p < 0.05). Severe bronchopulmonary dysplasia is not found in the interventional group, 26% of the patients in the control group have severe form of the disease (p = 0.001). Severe intraventricular hemorrhages are found in 11% of the infants in the therapeutic group and 28% in the control group (p = 0.06). CONCLUSION: Due to the changed protocol, we report increased survival of ELBW infants without severe chronic complications. The acute pulmonary injury, acquired in the perinatal period, is directly connected with the development of BPD. For this reason, all the changes that we introduced in our clinic (heat management, support of spontaneous breathing, “open up” lungs – high flow PEEP/CPAP, and LISA during spontaneous breathing) contribute to the lower frequency of severe chronic complications and high percentage of ELBW infants, who do not develop severe BPD.